(الدَور القانوني لوزارة الخارجية العراقية في معالجة أزمة المياه (سد أليسو انموذجاً - Farouk Yousef Zubairi; Mahmoud Mohamed Ali Mahmoud Edris (JiL Center Journals, 2024)
The function of water in the present age has evolved in use and It is no longer limited to drinking and irrigation but have been used as political and economic pressure, Given their importance, necessitated the need to regulate new rules It regulates how to exploit interstate water, From this point of view, the researcher will highlight the project of the Turkish Aliso damand the purpose of its creation, In addition to the impact of this project on the population of the Tigris basin in Iraq and the violation of international laws, As well as the role of the Iraqi Foreign Ministry in preventing his stay, Until an agreement is reached regulating the use of the Tigris and Euphrates rivers between Iraq, Syria and Turkey, The researcher concluded that the water crisis can be solved through joint international and regional efforts in which good intentions and faith in common interests, This will only be possible through the conclusion of legal agreements of an international character to be respected by the signatory parties.